PERSEPSI MASYARAKAT TERHADAP PELESTARIAN TRADISI BHEN-GHIBEN DALAM ADAT PERNIKAHAN MADURA - Laylatin Khoyrica Aris; Masrokhin Masrokhin (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The Bhen-Ghiben tradition in Gersik Putih Village, located in Gapura Subdistrict, Sumenep Regency, is a customary practice in which the groom delivers household furnishings to the bride's home as a symbolic gesture prior to the wedding ceremony. This delivery is accompanied by a verbal agreement between both parties, marking the handover and acceptance of the items. This research aims to describe the implementation of the Bhen-Ghiben tradition within Madurese wedding customs and to analyze community perspectives on its preservation in contemporary times. This study is a field-based qualitative research utilizing an empirical juridical approach. Data were gathered through interviews, observations, and documentation, and analyzed using descriptive-analytical techniques. The findings reveal that the Bhen-Ghiben tradition is a long-standing cultural heritage maintained across generations. It is typically carried out on the morning before the marriage contract (akad) is held, symbolizing the groom’s preparedness to assume his role as head of the household. The community perceives the preservation of this tradition as vital for safeguarding Madurese cultural identity and ensuring its transmission to future generations. Although a minority may express reservations, they generally opt for mutual deliberation between both families rather than rejecting the tradition outright.